MULTIPLE CRITIQUES AS A METHOD OF PROGRESSIVE MUSLIM THINKING CONFRONTING PLURALITY - Siti Amallia (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Substantially, the term progressive Muslim in Islamic discourse is not a new thing. Progressive Muslims are Muslims who have a forward and open mindset. There are three major missions carried out, such as justice, gender equality, and accepting plurality. The purpose of this study is to find the root cause of the problem of religious exclusivism and how the role of progressive Muslims in solving this problem. Because misunderstandings about the meaning of plurality can then give birth to an attitude of radicalism that endangers many people. As a result, Islam is interpreted as a religion that is hard and rigid because some people criticize it in a narrow and way. How should a progressive Muslim try to reconstruct his thinking in facing plurality according to Omid Safi? The researcher uses descriptive and interpretive methods to explain the problem of plurality and Omid Safi's theory is related to contemporary problems. This research is library research by utilizing reading sources such as books and journals. From the research, it is found that Omid Safi uses multiple critiques as a progressive Muslim thinking method. According to him, multiple criticism or double criticism is an attempt to criticize Western and Islamic thought. Constructive criticism is necessary. Not only criticizing the hegemony of the West, but progressive Muslims also need to be criticized if they display an attitude that tends to be rigid, dogmatic, and authoritarian towards plurality. Safi associates plurality with humanism and open knowledge. Seeing that humans have the same values justice is one of the elements that must be upheld. Safi defines plurality as a form that goes beyond tolerance (Beyond pluralism). According to him, there is still a distance between tolerance in accepting differences. Like a poison that can still be tolerated by the human body. Plurality is when we can say “we” even though we have different beliefs. In the end, the idea of ​​plurality encourages us to be humanist and dynamic towards the times.